1972
DOI: 10.1002/aja.1001330309
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of the pia mater of the rat

Abstract: Tissue from the central nervous system of 11 adult SpragueDawley rats fixed by vascular perfusion with buffered aldehydes was used in a study of the fine structure of the pia mater. Surface tissue from the cerebral and cerebellar cortices, ventral pons, olfactory bulb, tuber cinereum, spinal cord, superior colliculus, optic chiasm, and median longitudinal fissure was examined. Variations in pial composition occurred within each of these selected areas although a basic pattern prevailed throughout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

1974
1974
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 27 publications
1
25
2
1
Order By: Relevance
“…However, our data cannot demonstrate whether the IGF-II gene is active in all of the leptomeningeal cells, or in a specific subset [at least two, and possibly more, cellular types constitute the cell population of the leptomeninges (23,24,42)]. Also, our results do not prove that these cells are secretory, although this function is not unlikely.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…However, our data cannot demonstrate whether the IGF-II gene is active in all of the leptomeningeal cells, or in a specific subset [at least two, and possibly more, cellular types constitute the cell population of the leptomeninges (23,24,42)]. Also, our results do not prove that these cells are secretory, although this function is not unlikely.…”
Section: Resultscontrasting
confidence: 70%
“…The detection oftranscriptional activity ofthe rIGF-II gene in both the arachnoid and pial cells, which cannot be discriminated morphologically (22)(23)(24)(25), suggests that they share at least some common function. However, our data cannot demonstrate whether the IGF-II gene is active in all of the leptomeningeal cells, or in a specific subset [at least two, and possibly more, cellular types constitute the cell population of the leptomeninges (23,24,42)].…”
Section: Resultsmentioning
confidence: 99%
“…Our preparation had the advantage that the dura and the cranium were not open during the exper iment. The dura of the rat is a 2-5 f..l m thick trans lucent membrane containing very few blood vessels (Morse and Low, 1972); thus, it does not interfere with the LDF signal, as noted by others (Dirnagl et aI., 1989). It was suggested (Hundley et aI., 1988) that the sparsity of cerebral vasomotion was due to anesthesia.…”
Section: Methodological Considerationsmentioning
confidence: 59%
“…Indeed they transform from flat overlapping cells into fusiform or roundish cells provided with microvil lous-like processes. Several studies have demonstrated that the leptomeningeal sheath is composed of fibrocytelike cells [13][14][15] possessing a variable degree of reactiv ity and macrophagic activity against foreign materials and noxious stimuli [15,16]. In our case the changes in the leptomeninx may simply represent an early reaction of macrophage-like leptomeningeal cells to blood extrav asation in the overlying dura mater.…”
Section: Discussionmentioning
confidence: 82%